The World Bank’s Publication Record - Ravallion, Martin; Wagstaff, Adam (2012)
The World Bank has produced a huge volume of books and papers on development -- 20,000 publications spanning decades, but growing appreciably since 1990. This paper finds evidence that many of these publications have influenced development thinking, as indicated by the citations found using Google Scholar and in bibliographic data bases. However, the authors also find that a non-negligible share of the Bank's publications have received no citations, suggesting that they have had little scholarly influence, though they may well have had influence on non-academic audiences. Individually-authored journal articles have been the main channel for scholarly influence. The volume of the Bank's research output on development is greater than that of any of the comparator institutions identified, including other international agencies and the top universities in economics. The bibliometric indicators of the quality and influence of the Bank's portfolio of scholarly publications are on a par with, or better than, most of the top universities.